Parametric Push-Out Analysis on Perfobond Rib with Headed Stud Mixed Shear Connector - Shuangjie Zheng; Chen Zhao; Yangqing Liu (Advances in Civil Engineering)
In steel and concrete composite structures, it is unfavourable to install many headed studs or perfobond ribs with narrow spacings at the joints. To solve this problem, a new type of a mixed shear connector was developed by combining a headed stud and perfobond rib at the same steel beam flange. In this paper, totally nine push-out tests were conducted. The main purpose was to compare the failure mode and the load-slip behavior of the headed stud, perfobond rib, and mixed shear connector. Furthermore, 19 nonlinear finite element simulations were performed. The effects of connector dimension and material properties on the structural behaviors of mixed shear connectors were studied. Based on the experimental and parametric study, an analytical equation was finally proposed to evaluate the shear capacity of perfobond rib with a headed stud mixed shear connector.